Synergistic Effect of Acylpyrazolone Integrated with Multiwalled Carbon Nanotubes on the Electrochemical Analysis of Ascorbic Acid - Mohamad Syahrizal bin Ahmad, Illyas bin Md Isa, Norhayati binti Hashim, Mohamad Idris Bin Saidin (Tanjung Malim, 2024)
Synergistic Effect of Acylpyrazolone Integrated with Multiwalled Carbon Nanotubes on the Electrochemical Analysis of Ascorbic Acid by Mohamad Syahrizal bin Ahmad, Illyas bin Md Isa, Norhayati binti Hashim, Mohamad Idris Bin Saidin